Regional powers and regional security governance: An interpretive perspective on the policies of Nigeria and Brazil. (September 2015) - Lopez-Lucia, Elisa
The study of regional powers has become an increasingly prominent part of debates in the academic field of International Relations (IR), particularly regarding their role in creating the conditions for international security. While the IR literature tends to focus on the causal effect of material and ideational factors to explain the policy of regional powers, this article uses an interpretive approach, centring on the study of historical representations. Through a comparative analysis of the foreign policies of Brazil and Nigeria since the 1990s, it argues that a focus on the traditions and dilemmas of regional powers enables a better explanation of their policy, one which illustrates how material factors are refracted through the representations of foreign policy elites in the two countries and expressed in their foreign policy practices as regional powers.